Three new species of tiger beetles and new data on Cicindelina species from Angola (Coleoptera: Carabidae: Cicindelinae) - Serrano, Artur R.m.; Capela, Rúben A.; Oesterle, Andreas (Zootaxa, 2015)
Three new species of tiger beetles, two of the genus Trichotaenia Rivalier, 1957 and one of the genus Cylindera Westwood, 1831, subgenus Ifasina Jeannel, 1946 are described from Angola. An annotated list of species of Cicindelina sampled in this country is provided also. Records for three species previously unknow from Angola are given: Ophryodera smrzi Werner, 2005, Lophyra clatharta (Dejean, 1825) and Lophyra sumlini Cassola, 1976. Some considerations on the distribution and general ecology of these beetles in Angola are also presented. Further, two dichotomic keys are made available for the identification of Trichotaenia species with marked shoulders and Cylindera (Ifasina) species of western and southwestern Africa, respectively.